Theory of structures : fundamentals, framed structures, plates and shells - Marti, Peter, 1949-; Thrift, Philip (Berlin, Germany : Wiley : Ernst & Sohn, A Wiley Company, 2013)
This book provides the reader with a consistent approach to theory of structures on the basis of applied mechanics. It covers framed structures as well as plates and shells using elastic and plastic theory, and emphasizes the historical background and the relationship to practical engineering activities. This is the first comprehensive treatment of the school of structures that has evolved at the Swiss Federal Institute of Technology in Zurich over the last 50 years. The many worked examples and exercises make this a textbook ideal for in-depth studies. Each chapter concludes with a.
Introduction. The Purpose and Scope of Theory of Structures -- Brief Historical Background -- Fundamentals. Design of Structures -- Structural Analysis and Dimensioning -- Static Relationships -- Kinematic Relationships -- Constitutive Relationships -- Energy Methods -- Linear Analysis of Framed Structures. Structural Elements and Topology -- Determining the Forces -- Stress Resultants and State Diagrams -- Influence Lines -- Elementary Deformations -- Single Deformations -- Deformation Diagrams -- The Force Method -- The Displacement Method -- Continuous Models -- Discretised Models -- Non-Linear Analysis of Framed Structures. Elastic-Plastic Systems -- Limit Analysis -- Stability -- Plates and Shells. Plates -- Slabs -- Folded Plates -- Shells -- Appendix. A1: Definitions -- A2: Notation -- A3: Properties of Materials -- A4: Geometrical Properties of Sections -- A5: Matrix Algebra -- A6: Tensor Calculus -- A7: Calculus of Variations -- References -- Name Index -- Subject Index.
Includes bibliographical references and indexes.
Print version record.
Keywords: Structural analysis (Engineering); Structural design; TECHNOLOGY & ENGINEERING -- Structural; Structural analysis (Engineering); Structural design; Electronic books; Electronic books